An aerial survey of rhinoceros and elephant in a portion of the Chobe National Park and surrounding areas, northern Botswana, September 1992 - Michael Knight; P. Hitchins; K. Erb (Pachyderm)
During the 1992 dry season a low intensity total count aerial survey, using two aircraft simultaneously, was undertaken specifically for black and white rhino and elephant in northern Botswana. No black rhinos were recorded, while a total of seven white rhinos were counted in the survey. An approximate population figure of 14,758 elephants giving an estimated density of 1.15 per sq km for the areas as a whole was recorded. The relatively low carcass ratio of 3% is indicative of a population with low mortality and/or increased immigration.